Tax Incentives and Foreign Direct Investment in South Africa - Kransdorff, Michael (Consilience, 2010)
Foreign direct investment (FDI) has been identified as one of the key components required to stimulate economic growth—so much more so in a country like South Africa with sparse savings. Generous tax incentives are one of the most common policy instruments employed by governments, particularly those in the developing world, to attract much needed FDI. This report considers the importance of tax incentives as a determinant of FDI and their relevance for South Africa. An examination of the numerous studies (both qualitative and quantitative) on the effects of fiscal incentives on FDI reveals that although their influence is generally weak, they can under certain circumstances be a decisive factor in international investment decisions. When the investment fundamental of competing FDI locations are similar, the extent of the tax relief offered becomes an important consideration. Thus, given the uncompetitiveness of South Africa’s fiscal policies in comparison to those of similar emerging markets, tax incentives could be a possible remedy for the country’s FDI dearth.